(untitled) (Research, Society and Development, 2022)
Childhood obesity is considered a worldwide epidemic that is affecting children, and accompanied by excess weight, several complications arise such as diabetes mellitus, respiratory problems, systemic arterial hypertension and dyslipidemias that favor the appearance of cardiovascular diseases. Therefore, this article aimed to present what are the causes of obesity and preventive actions aimed at a better quality of life for these children and to evaluate nursing actions in the fight against obesity. The study is an integrative literature review, in which a query will be carried out on scientific articles selected through searches in the Scientific Electronic Library Online (SCIELO) database, Virtual Health Library. In order to explore the main themes, the following keywords were used: childhood obesity, prevention, health promotion, child development, child health. The inclusion criteria for the study were the approaches around childhood obesity and its context, scientific articles were detected and articles were used, between the years 2017 to 2022. The exclusion criteria were publications of thesis, dissertation, monograph and duplicate materials and articles not directly related to the research theme. As explained above about childhood obesity, it is noted that it is a major public health problem that has been affecting a large number of children, causing serious health problems.